Pemikiran Ibn Rushd tentang Pendidikan dan Relevansinya dengan Dunia Modern - Widia Putri (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2020)
This paper aims to analyzing the thought of a character (Ibn Rushd) to education, and its relevance to modern education. The research method used in this paper is content analysis. This paper uses a qualitative approach (library research) and then analyzes the sources that have been collected and then provides conclusions related to the material in the paper. The results showed that Ibn Rushd's concept of thinking leads to freedom of thought in developing science in the world of Islamic education without having to be limited to objects, be it exact or metaphysical; there is a compatibility between Ibn Rushd's education using the burhānī method with modern world education, it can be seen from the development of science in Islamic education.